2016
DOI: 10.1097/ta.0000000000001168
|View full text |Cite
|
Sign up to set email alerts
|

DUI histories in intoxicated injured bicyclists

Abstract: Epidemiologic study, level III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Some countries, such as Brazil (Gjerde et al, 2015) have contributed with a large number of research studies (Pechansky et al, 2010) but for most countries the evidence is scattered and not comparable. Most importantly, there is a paucity of evidence on the presence of alcohol in RTIs among pedestrians and non-driver riders, who are important victims of RTIs(du Plessis et al, 2016; Forson et al, 2016; Maximus et al, 2016; Senserrick et al, 2014; Sethi et al, 2016; Waller et al, 1986). …”
Section: Introductionmentioning
confidence: 99%
“…Some countries, such as Brazil (Gjerde et al, 2015) have contributed with a large number of research studies (Pechansky et al, 2010) but for most countries the evidence is scattered and not comparable. Most importantly, there is a paucity of evidence on the presence of alcohol in RTIs among pedestrians and non-driver riders, who are important victims of RTIs(du Plessis et al, 2016; Forson et al, 2016; Maximus et al, 2016; Senserrick et al, 2014; Sethi et al, 2016; Waller et al, 1986). …”
Section: Introductionmentioning
confidence: 99%
“…One factor in some intoxicated bicyclist collisions is a history of driving under the influence (DUI) in a motor vehicle, which in one study of 149 injured bicyclists in the emergency department, found 66 (44.2%) had prior driving under the influence convictions with suspension of driving privileges. 22 There appear to be opportunities for targeted injury prevention efforts for intoxicated bicyclists in our catchment, given the small geographic area. Unfortunately, we do not have data on owned bikes versus rented rideshare bikes which became ubiquitous at the end of the study period.…”
Section: Discussionmentioning
confidence: 99%
“…Surveys on alcohol and drugs on drivers provide valuable information on abuse patterns and trends, which help to establish new examination methods and legal limits as well as preventative measures. Numerous surveys on driving under the influence of alcohol and drugs were conducted worldwide through analyzing data from traffic offences and accidents as well as from roadside testing [ [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] ]. The surveys revealed that in addition to alcohol, drugs including cannabis, amphetamines and cocaine were frequently taken by the drivers, while polydrug uses were not rare.…”
Section: Surveillance In Toxicologymentioning
confidence: 99%